ENGLISH TEACHERS’ MISCONCEPTION ABOUT THE APPLICATION OF GENRE BASED APPROACH IN THE TEACHING OF ENGLISH WITHIN THE K-13 CURRICULUM OF INDONESIA - Berlin Sibarani (Journal of Language, Literature and Teaching, 2020)
Teacher is key variable of in the conception of teaching. His comprehensive knowledge and skills, governs the ways of the teaching implementation. Teachers’ misconception of what to teach and of approach to apply can be a determinant factor for the failure of the teaching and this is true to the teaching of English. The K-13 curriculum, requires the English teachers to teach English by taking genre as unitizing of lesson topics and as the base approach. In line with the teaching conception, the English teachers’ misconception is also regarded as determinant factor of failure in teaching English. To find out if the teaching of English based genre is implemented properly can be done by researching the English teachers’ misconception. Sixt English teachers’ classroom interaction were observed and took the transcript of the interaction as data. The data were analysed by applying the data analysis model proposed by Bogdan and Biddle. The results shows that there is a misconception among the English teachers about the nature of genre and the nature of genre based approach. This misconception is applied to implement the teaching of English and the misconception is reflected in the KD3 and KD4 formulation and in the activities organization which is very far away from the concept of the genre and the approach. Teaching English with genre based approach is not yet implemented properly and the improper implementation is caused by the misconception among the English teachers.       Keywords: misconception, genre, approach, teaching English